Selective N-oxidation of aromatic amines to nitroso derivatives using a molybdenum acetylide oxo-peroxo complex as catalyst - Biradar, Ankush V.; Kotbagi, Trupti V.; Dongare, Mohan K.; Shubhangi B. Umbarkar (Tetrahedron Letters, 2008)
The molybdenum acetylide oxo-peroxo complex obtained in situ by the treatment of the corresponding molybdenum acetylide carbonyl complex, CpMo(CO)(3)(C CPh); Cp = eta(5-)C(5)H(5) with H(2)O(2), has been used as an efficient catalyst for selective N-oxidation of primary amines to nitroso derivatives. Excellent amine conversion (up to 100%) and very high selectivity for nitroso compounds (99%) have been obtained using 30% hydrogen peroxide as an oxidant. The oxo peroxo, Mo(VI) complex has also been found to be very active for the oxidation of various substituted primary aromatic amines with electron donating as well as electron withdrawing substituents on the aromatic ring. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: aromatic amine; Homogenous catalyst; Hydrogen peroxide; Molybdenum complex; nitroso; Oxidation; Oxo-peroxo

Selective oxidation of nonrefractory and refractory sulfides by cyclopentadienyl molybdenum acetylide complexes as efficient catalysts - Chandgude, Macchindra G.; Biradar, Ankush V.; Kotbagi, Trupti V.; Puranik, Vedavati G.; Dongare, Mohan K.; Shubhangi B. Umbarkar (Catalysis Letters, 2012)
{The synthesis and catalytic properties of molybdenum acetylide complexes CpMo(CO)(3)(-C CR)
Keywords: Homogeneous catalysis; Molybdenum acetylide; Oxo-peroxo species; Refractory sulfide oxidation